MARTIN HEIDEGGER'S EXISTENTIALISM AS A PARADIGM IN ISLAMIC RELIGIOUS EDUCATION - Sutrisno, Shidiq Agung (At-Thullab : Jurnal Mahasiswa Studi Islam, 2025)
This research explores the application of Martin Heidegger's existentialist philosophy, especially the concept of Dasein, as a paradigm in Islamic Religious Education. This research examines how Heidegger's principles- self-awareness, freedom, and moral responsibility- can overcome the limitations of traditional dogmatic approaches in Islamic Religious Education, which often lack reflection. Using qualitative-descriptive methods and philosophical analysis, this research integrates Heidegger's existentialism with reflective pedagogy to offer an innovative teaching model. Data were collected through extensive literature observations and analyzed using qualitative content analysis, focusing on thematic reduction, categorization, and interpretation. Findings show that the existentialist approach fosters critical thinking and spiritual awareness, enabling students to authentically internalize Islamic values ​​and adapt them to modern challenges. This paradigm shifts the teaching of Islamic Religious Education. from rote memorization to a dialogical method, increasing moral responsibility and authentic self-development. Despite challenges such as resistance from traditional educators and curriculum limitations, this research highlights the transformative potential of existentialism in forming reflective and morally mature students.